2010
DOI: 10.1017/s0029665110001990
|View full text |Cite
|
Sign up to set email alerts
|

Drug disposition in obesity and protein–energy malnutrition

Abstract: Clinical response to medication can differ between patients. Among the known sources of variability is an individual's nutrition status. This review defines some pharmacokinetic terms, provides relevant body size metrics and describes the physiologic influences of protein-energy malnutrition and obesity on drug disposition. Weight-based drug dosing, which presumes a healthy BMI, can be problematic in the protein-energy malnourished or obese patient. The use of total body weight, lean body weight, or an adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 85 publications
(130 reference statements)
0
27
0
Order By: Relevance
“…In addition, several previous reports showed that the status of nutrition had an impact on the metabolism of the chemotherapeutic drugs. 29,30 For instance, nutritional status was reported to affect the level of cytochrome P450 enzymes which are responsible for the metabolism of the chemotherapeutic drugs. It was reported that there was a correlation between total body weight and plasma half-life of CY, which means that the concentration of CY is higher in obese patients compared with the normal weight patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several previous reports showed that the status of nutrition had an impact on the metabolism of the chemotherapeutic drugs. 29,30 For instance, nutritional status was reported to affect the level of cytochrome P450 enzymes which are responsible for the metabolism of the chemotherapeutic drugs. It was reported that there was a correlation between total body weight and plasma half-life of CY, which means that the concentration of CY is higher in obese patients compared with the normal weight patients.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Weight-based drug dosing regimens are not reflective of drug disposition in malnourished and obese patients. 31,33 This is further complicated when relying on body surface area or 'ideal' body weight rather than on more appropriate metrics for dosing medication. 31,34 The precipitating factor of an interaction may also be the drug itself.…”
Section: Types Of Drug and Nutrition Interactionsmentioning
confidence: 99%
“…Pharmacokinetic and pharmacodynamic data are much less frequently assessed based on nutrition status (eg, protein-calorie malnutrition, obesity, micronutrient deficits), although the influence on drug metabolism has been recognized previously (6,(65)(66)(67). Drug distribution and drug clearance are the two parameters most likely to be influenced by malnutrition, with the potential-if not recognized and addressed by modifying the initial dose or maintenance dose, respectively-to alter clinical response (68,69).…”
Section: Influence Of Nutrition Status On Drugsmentioning
confidence: 99%
“…One unfortunate aspect of weight-based dosing in practice is the use of empiric "ideal" body weight equations (75,76), or the incorporation of these tenuous values into an "adjusted" body weight equation. In the latter equation, the correction factor used is rarely drug-specific (69). An evidence-based estimate of lean body weight is suggested as a more appropriate metric in determining dosing weight for obese patients (69,77,78).…”
Section: Influence Of Nutrition Status On Drugsmentioning
confidence: 99%
See 1 more Smart Citation